Interferometric Study of Ionospheric Plasma Irregularities in Regions of Phase Scintillations and HF Backscatter - Andres Spicher; James LaBelle; John W. Bonnell; Roger Roglans; Chrystal Moser; Stephen A. Fuselier; Scott Bounds; Lasse B. N. Clausen; Francesca Di Mare; Connor A. Feltman; Yaqi Jin; Craig Kletzing; et al. (Geophysical Research Letters)
Abstract We investigate the nature of small‐scale irregularities observed in the cusp by the Twin Rockets to Investigate Cusp Electrodynamics‐2 (TRICE‐2) in regions of enhanced phase scintillations and high‐frequency coherent radar backscatter. We take advantage of the fact that the irregularities were detected by spatially separated probes, and present an interferometric analysis of both the observed electron density and electric field fluctuations. We provide evidence that fluctuations spanning a few decameters to about a meter have low phase velocity in the plasma reference frame and are nondispersive, confirming that decameter‐scale irregularities follow the E × B velocity. Furthermore, we show that these “spatial” structures are intermittent and prominent outside of regions with strongest precipitation. The observations are then discussed in the context of possible mechanisms for irregularity creation.